PELAKSANAAN CORPORATE SOCIAL RESPONSIBILITY (CSR) PT. ARARA ABADI PADA BADAN USAHA MILIK KEPENGHULUAN (BUMKEP) TUAH SERANTAU KEPENGHULUAN RANTAU BAIS KECAMATAN TANAH PUTIH KABUPATEN ROKAN HILIR TAHUN 2017 - Akbar "; Raja Muhammad Amin (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
This study aims to determine the implementation of Corporate Social Responsibility (CSR) of PT. Arara Abadi at a business owned by on (BUMKep) Tuah Serantau Kepenghuluan Rantau Bais, Tanah Putih District, Rokan Hilir Regency. The problem of this research is the assistance of Corporate Social Responsibility (CSR) conducted by PT. Arara Abadi at the Tuah Serantau State Owned Enterprise (BUMKep) did not have a positive impact.               This research is a descriptive study with a qualitative approach. The types of data are primary data and secondary data, primary data obtained directly from the informant. Meanwhile secondary data is supporting data or strengthening primary data. Data collection techniques carried out by interview and documentation. Data analysis techniques in this study used the Miles and Huberman model, which included data reduction, data presentation, and drawing conclusions.                             The results of this study indicate that the Implementation of Corporate Social Responsibility (CSR) of PT. Arara Abadi at the Tuah Serantau State Owned Enterprise (BUMKep) has been running with. But the Corporate Social Responsibility (CSR) assistance of PT. Arara Abadi at the Tuah Serantau State Owned Enterprise (BUMKep) did not give a positive impact on the welfare of the community. As for the obstacles to the success of the implementation of Corporate Social Responsibility (CSR) in this Entrepreneurship-Owned Enterprise is the Director of BUMKep, Experience and understanding of the Beneficiary, Weather and Land Availability Group. From these constraints resulted in the Implementation of Corporate Social Responsibility (CSR) of PT. Arara Abadi at the Teng Serantau State Owned Enterprise (BUMKep) Tuah Serantau did not have a positive impact on the welfare of the Rantau Bais Kepenghuan community.Keywords: Implementation, CSR, BUMKep